From spillover to systems: evidence gaps in One Health preparedness for emerging infectious diseases in Latin America and the Caribbean - Esteban Ortiz-Prado; María Paz Cadena; Jorge Vasconez-Gonzalez; Juan S. Izquierdo-Condoy (Frontiers in Medicine, 2026)
Latin America and the Caribbean are a global hotspot for emerging and re-emerging infectious diseases, yet regional One Health preparedness remains uneven and incompletely operationalized. This narrative Mini Review synthesizes evidence published mainly between 2015 and 2026 on One Health preparedness for emerging infectious diseases in the region, emphasizing how environmental disruption and climate change shape zoonotic and vector-borne spillover risk. Available regional surveys suggest broad professional familiarity with the One Health concept but limited operational implementation, with environmental health frequently identified as the least-integrated domain. We argue that spillover risk—and the failure to detect and contain spillover once it occurs—should be understood as a system-level outcome shaped by ecological disruption, socioeconomic vulnerability, surveillance capacity, and governance, rather than as an isolated biological event: deforestation, agricultural and extractive expansion—including illegal mining and logging—unplanned urbanization, and climate variability generate new human–animal–vector interfaces, while fragmented governance, uneven and poorly decentralized laboratory capacity, and limited reservoir and environmental surveillance leave these interfaces unmonitored. Environmental and climatic drivers are robustly linked to spillover, although the pathways are disease-specific rather than universal, and socioeconomic vulnerability concentrates the resulting burden in Indigenous, rural, and marginalized populations. We identify priority gaps in integrated surveillance, decentralized diagnostics, genomic capacity, reservoir ecology, governance, financing, and equity, and propose an agenda for anticipatory, climate-informed, and context-sensitive preparedness.